2021
DOI: 10.1103/physrevb.103.224307
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative phonon scatterings and the two-channel thermal transport in Tl3VSe4

Abstract: We study the role of nonperturbative phonon scattering in strongly anharmonic materials having ultralow lattice thermal conductivity with unusual temperature dependence. We take Tl 3 VSe 4 as an example and investigate its lattice dynamics using perturbation theory (PT) up to the fourth order and molecular dynamics (MD) with a machine-learning potential. We find distinct differences of phonon linewidth between PT and MD in the whole Brillouin zone. The comparison between the theoretical phonon linewidths and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…The predictions by NEP agree well with the experimental data [91,92]. BTE calculations with force constants from DFT [90] or the GAP-SOAP potential [59] considering both three-phonon and four-phonon scatterings also produce comparable results. However, if only three-phonon scattering is considered in the BTE calculations [90], the obtained lattice thermal conductivity values are about two times as large.…”
Section: B Thermal Transport In Bulk Pbtesupporting
confidence: 76%
See 4 more Smart Citations
“…The predictions by NEP agree well with the experimental data [91,92]. BTE calculations with force constants from DFT [90] or the GAP-SOAP potential [59] considering both three-phonon and four-phonon scatterings also produce comparable results. However, if only three-phonon scattering is considered in the BTE calculations [90], the obtained lattice thermal conductivity values are about two times as large.…”
Section: B Thermal Transport In Bulk Pbtesupporting
confidence: 76%
“…This indicates the importance of four-phonon scattering in PbTe. In some other materials such as Tl 3 VSe 4 , it has been suggested that the perturbation theory as adopted in the BTE approach can severely underestimate the phonon scatterings even when four-phonon scattering is included [59]. Because phonon anharmonicity is fully taken into account in MD simulations, we expect that our efficient NEP potential will serve as a promising tool for investigating heat transport properties in materials with strong phonon anharmonicity.…”
Section: B Thermal Transport In Bulk Pbtementioning
confidence: 97%
See 3 more Smart Citations